2002
DOI: 10.1111/j.1349-7006.2002.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Expression and Estrogen Receptor‐independent Cytotoxic Effects of Tamoxifen on Malignant Rhabdoid Tumor Cells in vitro

Abstract: Key words: Malignant rhabdoid tumor -Estrogen receptor -Antiestrogen -ApoptosisEstrogens have long been recognized to play important roles in the growth and differentiation of reproductive and non-reproductive tissues.1, 2) It has also become clear that most breast cancers are dependent on estrogens for growth and progression, and this has been the basis for continuing interest in the role of estrogen receptor (ER) in the prognosis of this devastating disease. However, some recent reports have demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Consistent with the previous findings, treatment of MON cells with 10 mM or less of 4OH-Tam alone did not drastically inhibit the survival, whereas concentrations above 10 mM resulted in rapid cell death ( Figure 3a) (Koshida et al, 2002). Therefore, we tested the effect of combination of 4-HPR with 10 mM 4OH-Tam for various times of exposure ( Figure 3b).…”
Section: Oh-tam Augments the 4-hpr-induced Growth Arrest Of Rt Cellssupporting
confidence: 80%
“…Consistent with the previous findings, treatment of MON cells with 10 mM or less of 4OH-Tam alone did not drastically inhibit the survival, whereas concentrations above 10 mM resulted in rapid cell death ( Figure 3a) (Koshida et al, 2002). Therefore, we tested the effect of combination of 4-HPR with 10 mM 4OH-Tam for various times of exposure ( Figure 3b).…”
Section: Oh-tam Augments the 4-hpr-induced Growth Arrest Of Rt Cellssupporting
confidence: 80%
“…The results for these six MRT cell lines was confirmed with both histopathology and electron microscopy. 3,10,[17][18][19][20] Aberration of the hSNF5/INI1 gene was also detected in the six MRT cell lines. 22) 5-Aza-CR was utilized to examine the expression of several muscle markers.…”
Section: Discussionmentioning
confidence: 87%
“…7,[17][18][19][20][21] Recently, Sugimoto et al 21) reported a smooth muscle phenotype in an MRT cell line. Steahelin et al 25) reported MyoD expression in bone marrow metastasis of extrarenal MRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations